2004
DOI: 10.1007/s00394-004-0439-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the stage of lactation in humans on carotenoid levels in milk, blood plasma and plasma lipoprotein fractions

Abstract: In mammals the composition of milk changes during early lactation, with a rapid decline of fat-soluble vitamins and a continuous increase in total lipids. The mechanisms underlying this phenomenon are not well understood, but might involve selective mechanisms related to mammary uptake or secretion into the milk. Since carotenoids are specifically distributed among the lipoprotein fractions in plasma, the simultaneous determination of carotenoids in plasma, lipoprotein fractions and milk might offer an opportu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
103
2
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(140 citation statements)
references
References 33 publications
28
103
2
4
Order By: Relevance
“…Daily supplementation with MV (vitamins B, C and E) increased a-tocopherol concentrations in breast milk by approximately 20% while MV supplementation was associated with a B25% reduction in breast milk concentrations of g-tocopherol. In the placebo group, the concentrations of retinol, b-carotene, a-carotene and the tocopherols were comparable to those reported from studies in nonsupplemented, presumably HIV-uninfected women at similar times postpartum (Gossage et al, 2002;Canfield et al, 2003;Schweigert et al, 2004;Sakurai et al, 2005).…”
Section: Discussionsupporting
confidence: 66%
“…Daily supplementation with MV (vitamins B, C and E) increased a-tocopherol concentrations in breast milk by approximately 20% while MV supplementation was associated with a B25% reduction in breast milk concentrations of g-tocopherol. In the placebo group, the concentrations of retinol, b-carotene, a-carotene and the tocopherols were comparable to those reported from studies in nonsupplemented, presumably HIV-uninfected women at similar times postpartum (Gossage et al, 2002;Canfield et al, 2003;Schweigert et al, 2004;Sakurai et al, 2005).…”
Section: Discussionsupporting
confidence: 66%
“…However, the plasma vitamin A concentrations for the formula-fed baby and the breast-fed baby are comparable (Ghebremeskel et al 1999). Breast milk contains the whole spectrum of carotenoids present in the human diet and serum (Khachik et al 1997;Canfield et al 2003;Schweigert et al 2004), while milk formulas contain no carotenoids, very low concentrations of carotenoids or a limited variety of carotenoids (Sommerburg et al 2000).…”
Section: Human Breast Milk V Milk Formulasmentioning
confidence: 99%
“…1,2 The nutritional composition of colostrum is particularly distinct, being rich in liposoluble vitamins. 3 In addition to being influenced by the stage of lactation, the vitamin A contained in breastmilk may be altered by the fat content, as each feed progresses, and by factors specific to individual nursing mothers. [4][5][6][7][8][9] Despite the great variation in retinol levels in colostrum, some authors have suggested that it could be used as an indicator of vitamin A nutritional status, since analyzing the nutrient in milk is non-invasive and access is easier.…”
Section: Introductionmentioning
confidence: 99%